2018
DOI: 10.3389/fpsyg.2018.00783
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in How Family Income and Parental Education Relate to Reading Achievement in China: The Mediating Role of Parental Expectation and Parental Involvement

Abstract: The impact of social economic status (SES) on children's academic outcomes has been well documented. However, the mechanisms underlying this relationship remain poorly understood. Furthermore, the process by which SES relates to academic achievement needs to be studied separately for boys and girls. Using a sample of 598 Chinese children (299 boys, 299 girls) in grades 4 to 6 and their parents, this study examined the process of how family SES, specifically family income and parental education, indirectly rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 62 publications
6
50
0
Order By: Relevance
“…Likewise, in a comparison of TIMMS arithmetic data from two HK cohorts, Guo, Marsh, Parker, Morin and Yeung (2015) found that SES showed similarly small positive associations with males' and females' TIMMS scores (weighted mean effect size = .11). In contrast, a later study of 598 elementary school children from China, Guo et al (2018) found that links between SES and literacy differed for boys and girls. Specifically, while parental education showed direct effects on literacy for both genders, family income had direct effects on literacy for females, but was indirectly related to literacy (via parent-child communication) for males.…”
Section: Ses Executive Functions and Mathmentioning
confidence: 81%
“…Likewise, in a comparison of TIMMS arithmetic data from two HK cohorts, Guo, Marsh, Parker, Morin and Yeung (2015) found that SES showed similarly small positive associations with males' and females' TIMMS scores (weighted mean effect size = .11). In contrast, a later study of 598 elementary school children from China, Guo et al (2018) found that links between SES and literacy differed for boys and girls. Specifically, while parental education showed direct effects on literacy for both genders, family income had direct effects on literacy for females, but was indirectly related to literacy (via parent-child communication) for males.…”
Section: Ses Executive Functions and Mathmentioning
confidence: 81%
“…Interpreted within the broader child development literature, these findings corroborate past research that found significantly higher levels of cognitive functioning and executive functioning in children whose parents had a higher level of education, compared to children whose parents had a lower level of education [64,65]. Parents with higher educational attainment may be more involved in their children's school education (e.g., discuss school activities/performance with the child, monitor the child's use of time), which in turn may facilitate children's cognitive development and academic achievement [66]. Furthermore, studies have found that parents' higher cognitive abilities, such as intelligence quotient (IQ), are associated with better language and cognitive outcomes in children, suggesting the possible intergenerational transmission of cognitive abilities [67].…”
Section: Discussionmentioning
confidence: 99%
“…Little is known, however, about the strength of the relationship of these critical factors with reading comprehension when studied jointly in a multilevel model. Furthermore, there is a lack of empirical studies on mechanisms underlying the relationship between critical factors and students' reading comprehension in secondary school (Slavin, Cheung, Groff, & Lake, 2008;Guo et al, 2018). Consequently, the present study intends to address the resulting call for this research in Chinese secondary school.…”
Section: Correlates Of Reading Comprehensionmentioning
confidence: 97%
“…However, during the process of rapid urbanization, reading teaching faces several dilemmas although Chinese education witnesses a great success in the past three decades. First, students from poor families may fail to develop their reading competence because of the social economic status of their families (Guo et al, 2018). They are not interested in reading classes.…”
Section: Contextual Backgroundmentioning
confidence: 99%